2002
DOI: 10.1590/s0100-879x2002000900009
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7) improves the post-ischemic function in isolated perfused rat hearts

Abstract: We evaluated the effects of angiotensin-(1-7) (Ang-(1-7)) on postischemic function in isolated hearts from adult male Wistar rats perfused according to the Langendorff technique. Local ischemia was induced by coronary ligation for 15 min. After ischemia, hearts were reperfused for 30 min. Addition of angiotensin II (Ang II) (0.20 nM, N = 10) or Ang-(1-7) (0.22 nM, N = 10) to the Krebs-Ringer perfusion solution (KRS) before the occlusion did not modify diastolic or systolic tension, heart rate or coronary flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 37 publications
5
69
0
1
Order By: Relevance
“…5 A large body of evidence has accumulated over the past two decades to support the notion that angiotensin II, through its AT1 receptor, mediates myocardial interstitial fibrosis and cardiomyocyte hypertrophy, 9,10 but it does not directly stimulate cardiomyocytes growth and fibrosis in the adult myocardium, but does so indirectly by inducing the expression of TGF-b, which then acts locally through the auto/paracrine mechanism. 11,12 TGF-b is a locally generated cytokine that has been implicated as a major contributor to tissue fibrosis in various organ systems. 13 Antagonists of the RAS, such as ACE inhibitors and angiotensin-receptor blockers, attenuate the fibrotic changes and matrix deposition mediated by TGF-b.…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A large body of evidence has accumulated over the past two decades to support the notion that angiotensin II, through its AT1 receptor, mediates myocardial interstitial fibrosis and cardiomyocyte hypertrophy, 9,10 but it does not directly stimulate cardiomyocytes growth and fibrosis in the adult myocardium, but does so indirectly by inducing the expression of TGF-b, which then acts locally through the auto/paracrine mechanism. 11,12 TGF-b is a locally generated cytokine that has been implicated as a major contributor to tissue fibrosis in various organ systems. 13 Antagonists of the RAS, such as ACE inhibitors and angiotensin-receptor blockers, attenuate the fibrotic changes and matrix deposition mediated by TGF-b.…”
Section: Angiotensin (1à7) Prevent Heart Dysfunction and Left Ventricmentioning
confidence: 99%
“…11 It has also been found that Ang (1-7) have a cardioprotective effect in the rat. Ang (1-7) decrease the incidence and duration of ischemia/reperfusion arrhythmias 12 and improve post-ischemic function in the isolated rat heart. 13 Angs (1-7) are also effective in preventing heart failure after myocardial ischemia, induced by left coronary artery ligation.…”
Section: Introductionmentioning
confidence: 99%
“…1] by our laboratory in 1988 (Schiavone et al 1988) and the cloning of ACE2 in 2000 (Donoghue et al 2000;Tipuis et al 2000) have led to a new perception of the intrinsic mechanisms through which the RAS regulates homeostasis. Ang-(1-7) is a downstream heptapeptide product of the system that can regulate blood pressure (Benter et al 1995b;Ferrario et al 2005), cardiac function (Ferreira et al 2002;Loot et al 2002;De Mello et al 2004), and cell growth (Tallant et al 2005).…”
Section: Angiotensin-(1-7) 163mentioning
confidence: 99%
“…7 In addition to its vascular effects, it was shown that Ang-(1-7) also has beneficial effects on cardiac function. [9][10][11] Moreover, it opposes the growth-stimulating effects of Ang II in vascular smooth muscle cells 12 and cardiomyocytes. 13 Ang-(1-7) also demonstrates effects on renal function by participating in the control of water and electrolyte homeostasis.…”
Section: Introductionmentioning
confidence: 99%